2013
DOI: 10.5897/ajb2012.3017
|View full text |Cite
|
Sign up to set email alerts
|

DNA profiling of commercial chilli pepper (Capsicum annuum L.) varieties using random amplified polymorphic DNA (RAPD) markers

Abstract: In the present study, genetic variability in 10 commercial chilli pepper varieties viz. Gemini,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The similarity of the genome sequences of some of these mutants indicates the stability of the mutants. The same thing was shown by Prasad et al (2013) who found that there were variations in the RAPD's band profile associated with morphological variations of chili peppers collected from Andhra Pradesh India, while the similarity of the band profile was related to the similarity of several morphological characters such as flower color, fruit size, and fruit orientation. Rêgo et al (2011) also found that RAPD markers were effective in detecting the genetic diversity among 29 hot pepper accessions from Brazil.…”
Section: Polymorphism Of Mutant G7/01 and Initial Line Based On Rapd ...supporting
confidence: 64%
“…The similarity of the genome sequences of some of these mutants indicates the stability of the mutants. The same thing was shown by Prasad et al (2013) who found that there were variations in the RAPD's band profile associated with morphological variations of chili peppers collected from Andhra Pradesh India, while the similarity of the band profile was related to the similarity of several morphological characters such as flower color, fruit size, and fruit orientation. Rêgo et al (2011) also found that RAPD markers were effective in detecting the genetic diversity among 29 hot pepper accessions from Brazil.…”
Section: Polymorphism Of Mutant G7/01 and Initial Line Based On Rapd ...supporting
confidence: 64%
“…Genomic DNA was isolated from acclimated plantlets of R. tetraphylla (seven plants were selected randomly, four from leaf callus based and three from stem callus based regenerants) from field along with the mother plant. Fresh leaf tissue (500 mg) of both mother plant and in vitro regenerated plants was used as raw material for DNA isolation by following modified cetyl trimethyl ammonium bromide (CTAB) method [28, 29]. The quality parameters of DNA were checked by spectrometric and electrophoretic methods.…”
Section: Methodsmentioning
confidence: 99%
“…RAPD primers were earlier reported for both DNA profiling and genetic fidelity studies in several plant species. Prasad et al 26 has reported DNA profiling of chilli peppers by using RAPD primers. Similarly, RAPD primers were used for analyzing genetic fidelity of Populus deltoides 27 , Morus alba 28 , Swertia chirayita 29 .…”
Section: Results and Discussion:-mentioning
confidence: 99%